The Rainbow Rift: LGBTQ+ Inclusivity and Wellbeing in the Ballet World - Rhiannon J. Watkin-Fairless; Ilana Seager van Dyk (Journal of Dance Medicine & Science, 2026)
Introduction: While the performing arts are often considered a safe space for LGBTQ+ individuals, classical ballet reflects gender disparities, with gay men highly visible and others comparatively underrecognised. Empirical research on LGBTQ+ ballet dancers remains limited. This study explored sexual orientation and gender identity (SOGI) demographics in an international sample of professional ballet dancers and examined differences in wellbeing by LGBTQ+ status using measures of workplace authenticity and wellbeing. Methods: Professional ballet dancers (N = 158) across 23 countries completed an online questionnaire. Descriptive statistics examined SOGI distribution. Independent-sample t -tests compared psychological distress, flourishing, disordered eating symptoms, holistic wellbeing, and authenticity between LGBTQ+ (n = 89) and non-LGBTQ+ participants (n = 69).Additional t -tests and mediation analyses compared outcomes in LGBTQ+ men (n = 21) and LGBTQ+ non-men (n = 68). Results: Overall, 68% of men and 48% of women identified as LGBTQ+; 18% of participants identified outside traditional binary genders. No significant differences in wellbeing emerged between LGBTQ+ and non-LGBTQ+ participants. Within the LGBTQ+ subgroup, men reported significantly lower psychological distress and disordered eating, and significantly higher workplace authenticity than non-men; and authenticity mediated the relationship between gender and wellbeing. Conclusion: LGBTQ+ representation in ballet is substantial, but findings suggest that visibility remains skewed toward men. Gender-based disparities in wellbeing and authenticity highlight systemic dynamics that privilege men over women and non-binary dancers. The term rainbow rift is proposed to describe this divide. Further research and interventions are recommended to foster a more inclusive ballet industry that embraces SOGI diversity.